REPRESENTASI SOSIAL BEAUTY STANDARD DI INDONESIA PADA FOLLOWERS INSTAGRAM FEMALE DAILY (@femaledailynetwork) - Nazhifah Dhiya Ananto (2024)
As technology advances and time passes, the concept of beauty has evolved under the influence of social media. Social media introduces beauty standards from other countries, which can influence people's perceptions. The purpose of this study is to examine the perception and social representation of beauty standards in Indonesia among Instagram followers of Female Daily, one of the largest beauty communities in Indonesia. The study employs social representation theory. This study employs a descriptive mixed-methods approach, utilizing both quantitative and qualitative data. The study population and sample consist of followers of the Female Daily Instagram account. The research findings indicate that when these followers hear the word 'beautiful', they associate it with three words: clean, beautiful, and white. The data collection results led to the formation of a typology comprising three types: type I, which is characterized by cleanliness; type II, which is characterized by beauty; and type III, which is characterized by whiteness.